Cross-Correlation Analysis of Line Laser High-speed Inertial Profilers. Issue 5 (May 2020) - Borelli, Noah; Choubane, Bouzid; Greene, James; Holzschuher, Charles; Fletcher, James
Thirteen different line-laser high-speed inertial profilers from four different manufacturers were recently tested at the Florida Department of Transportation (FDOT) Inertial Profiler Test Track. The hot-mix asphalt (HMA) track incorporates both dense and open-graded sections with international roughness index (IRI) values ranging from 34 to 104 in./mi. A cross-correlation analysis was performed on the resulting ride data. The accuracy comparison was performed using a SurPro reference profiler. The profilers as a group met the AASHTO R 56 cross-correlation criteria on each section except on a smooth, open-graded section. The profilers as a group met the repeatability cross-correlation on this section, but did not meet the accuracy cross-correlation requirement. This paper presents a description of the testing program, data collection efforts and subsequent analyses and findings.